Relapse Prevention Intervention after Suicidal Event (RISE): Feasibility study of a psychotherapeutic short-term program for inpatients after a recent suicide attempt - Bahlmann, Lydia; Lübbert, Marlehn B. J. S.; Sobanski, Thomas; Kastner, Ulrich W.; Walter, Martin; Smesny, Stefan; Wagner, Gerd (Frontiers in Psychiatry, 2022)
Recent research suggests that treating only mental disorders may not be sufficient to reduce the risk for future suicidal behavior in patients with a suicide attempt(s). It is therefore necessary to pay special therapeutic attention to past suicidal acts. Thus, the newly developed RISE (Relapse Prevention Intervention after Suicidal Event) program was built on the most effective components of existing psychotherapeutic and psychosocial interventions according to our current meta-analysis. The RISE program consists of five individual sessions designed for the acute psychiatric inpatient setting. The main goals of the treatment are to decrease future suicidal events and to improve patients’ ability to cope with future suicidal crises. In the present study, feasibility and acceptance of the RISE program were investigated as well as its clinical effects on suicidal ideations, mental pain, self-efficacy and depressive symptoms. We recruited a sample of 27 inpatients of the Department of Psychiatry and Psychotherapy, University Hospital Jena, Germany. The final sample consisted of 20 patients hospitalized for a recent suicide attempt, including 60 percent of multiple attempters. The data collection included a structured interview and a comprehensive battery of questionnaires to evaluate the feasibility and acceptance of the RISE program as well as associated changes in clinical symptoms. A follow-up examination was carried out after six months. Considering the low dropout rate and the overall positive evaluation, the RISE program was highly accepted in a sample of severely impaired patients. The present study also demonstrated that the levels of suicidal ideations, mental pain, depressive symptoms, and hopelessness decreased significantly after RISE. Since all of these clinical parameters are associated with the risk of future suicidal behavior, a potential suicide-preventive effect of the intervention can be inferred from the present findings. The positive results of the follow-up assessment after 6 months point in the same direction. In addition, RISE treatment increased self-efficacy in patients, which is an important contributor for better coping with future suicidal crises. Thus, present study demonstrate that RISE is a suitable therapy program for the treatment of patients at high risk for suicidal behavior in an acute inpatient setting.